AC-X: Characteristic Antinuclear Antibody Patterns of Two Anti-Mi-2 Autoantibody-Positive Dermatomyositis Patients—A Case Report - Wu, Ziyan; Xu, Honglin; Zhang, Shulan (Frontiers in Immunology, 2022)
Here we reported two anti-Mi-2 autoantibody-positive dermatomyositis (DM) patients with a characteristic antinuclear antibody (ANA) immunofluorescence pattern. Autoantibodes were screened by indirect immunofluorescence (IIF) on HEp-2 cells (Euroimmun, Lübeck, Germany) and confirmed by line immunoblot (ANA Profile 3—Euroimmun, Germany). These two patients were positive for ANA (speckled, titer 1:320), followed by confirmation of positive anti-Mi-2α and anti-Mi-2β positive and negative for all other antibodies. We found a characteristic ANA pattern of the anti-Mi-2 antibody that differed from the AC-4 pattern, especially in the morphology of mitotic cells (metaphase, anaphase, and telophase). Thus, we would like to suggest reporting this characteristic antinuclear antibody pattern as a new AC type, as AC-X.